Rhetoric in Advertising: A Study of Samsung Galaxy 24 FE Advertisement on Youtube - Raysa Purba; Mega Uli Arta Silitonga; Naomi Sephania br. Sirait; T. Thyrhaya Zein (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This study analyzes the rhetorical strategies in Samsung’s Galaxy S24 FE advertisement on YouTube, examining how diction, persuasion techniques, and language style appeal to a broad audience. Through qualitative content analysis, the research categorizes diction into denotative and connotative meanings and general and specific terms to understand how Samsung communicates product attributes clearly and persuasively. Persuasive techniques include rationalization, identification, suggestion, conformity, and compensation. Samsung’s language style, characterized by alliteration, assonance, and anastrophe, and Samsung’s repetition language style, characterized by epistrophe, reinforces product qualities and aids memorability. The results reveal that Samsung effectively combines direct, relatable language with emotional and logical appeals, positioning the Galaxy S24 FE as a product that meets diverse lifestyle needs. This study contributes insights into the role of rhetoric in digital advertising, highlighting methods for effective consumer engagement and brand positioning.